Influence of Processing in the Phenolic Composition and Health‐Promoting Properties of Lentils (Lens culinaris L.). Issue 5 (15th September 2016) - López, A.; El‐Naggar, T.; Dueñas, M.; Ortega, T.; Estrella, I.; Hernández, T.; Gómez‐Serranillos, M.P.; Palomino, O.M.; Carretero, M.E.
Abstract: Lentils ( Lens culinaris L.) are a source of polyphenolic compounds with health‐promoting properties, but cooking processes before consumption cause hydrolytic reactions, endogenous enzymes and biochemical metabolism activation which could interfere with their positive physiological effects. The aim of this study was to assess the influence of boiling and germination in the phenolic content and composition of marketed lentils by liquid chromatography analysis and thus, to evaluate its impact on the neuroprotective and anticancer properties through cell culture assays. The protective effect toward astrocyte culture when submitted to an oxidant injury remained after processing while a decrease in the antioxidant activity by oxygen radical absorbing capacity assay and DPPH methods was detected. Every sample was cytotoxic on the assayed cancer cell lines, the strongest antiproliferative activity being for germinated lentils on melanoma cell line. In conclusion, processing of lentils led to significant chemical modifications in the polyphenolic content without significant influence on its healthy properties. Practical Applications: This study assesses the influence of two cooking processes for legumes, boiling and germination, in the phenolic content and composition of lentils and its impact on health promoting properties mainly mediated by antioxidant activity. Both processes caused significant changes in the chemical composition which was reflected as a decrease in the antioxidant in vitro activity while neuroprotective effect remained. Every sample showed antitumoral activity toward the assayed cell lines, the strongest antiproliferative activity being obtained for germinated lentils on melanoma cell line. In conclusion, processing lentils before human consumption does not decrease the health‐promoting properties of this legume. Further studies to obtain food derivatives with a right balance among palatability, digestibility and antioxidant ability are desirable.